2023
DOI: 10.1021/acs.chas.3c00039
|View full text |Cite
|
Sign up to set email alerts
|

Molecules Featuring the Azaheterocycle Moiety toward the Application of Flame-Retardant Polymers

Shaolin Lu,
Shuidong Chen,
Lili Luo
et al.

Abstract: Flame retardancy is a desirable property of polymer materials, and the molecular design of novel flame-retardant structures considers three main aspects: (i) the chemical structure should have suitable thermal degradation temperature and a high tendency to form char; (ii) the flame-retardant molecule should not compromise the mechanical properties of the polymer matrix; and (iii) the molecule should have low inherent toxicity and generate minimal or no harmful substances to humans and the environment during de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…16 Additionally, the noncombustible gas generated from decomposition serves to dilute oxygen and other combustible gases, thus facilitating flame retardancy. 17 It has been verified in previous studies that the isocyanurate ring structure shows excellent thermal stability and charring characteristics in combustion. In this case, isocyanurates are considered to be potential in the construction of intrinsic flame retarded polymer materials.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…16 Additionally, the noncombustible gas generated from decomposition serves to dilute oxygen and other combustible gases, thus facilitating flame retardancy. 17 It has been verified in previous studies that the isocyanurate ring structure shows excellent thermal stability and charring characteristics in combustion. In this case, isocyanurates are considered to be potential in the construction of intrinsic flame retarded polymer materials.…”
Section: Introductionmentioning
confidence: 71%
“…N‐containing components exhibit significant heat absorption during the combustion, thereby effectively cooling the polymer surface 16 . Additionally, the noncombustible gas generated from decomposition serves to dilute oxygen and other combustible gases, thus facilitating flame retardancy 17 . It has been verified in previous studies that the isocyanurate ring structure shows excellent thermal stability and charring characteristics in combustion.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…While they can inhibit combustion, they also produce toxic substances such as dioxins, bromides, and chlorides, which degrade the base material's strength, heat resistance, and other properties [79][80][81]. Common nitrogen-based flame retardants include carbamates [82,83], phosphorus-nitrogen mixed flame retardants [84], and nitrogen heterocyclic compounds [85]. However, practical application has revealed that these flame retardants can produce nitrogen oxides and other pollutants.…”
Section: Flame Retardant Mechanism Of Black Phosphazene As Various Fl...mentioning
confidence: 99%
“…Aza-heterocycles and their derivates are commonly used to modify fabric surfaces for flame retardancy through endothermic decomposition [ 21 , 22 , 23 ]. This process releases non-combustible gases, such as nitrogen oxides, NH 3 , CO 2 and H 2 O, which dilute the concentration of oxygen and fuel gas on the fabrics [ 24 ]. They also encourage condensed phase char formation with nitrogen content.…”
Section: Introductionmentioning
confidence: 99%